Individual Sweet Bran Components in High-Forage Rations Fed to Holstein Steers Contribute to Changes in Nutrient Digestibility - Ludmila de Souza Monteiro; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: The ruminal and total tract digestibility of high-forage diets containing individual components of Sweet Bran (corn germ meal, corn bran, and corn steep liquor) fed to Holstein steers were evaluated. Study Description: Sweet Bran (Cargill Corn Milling, Blair, NE) is a wet corn gluten feed product that consists of a proprietary blend of corn bran, corn germ meal, and corn steep liquor. This study was conducted to evaluate the effect of the individual components of Sweet Bran on digestion. Twelve cannulated Holstein steers were housed at the Kansas State University Feed Intake Facility with continuous access diets presented in automated feed bunks and were divided into four groups with different diets: 1) Control (no Sweet Bran components); and diets containing 2) corn germ meal (germ); 3) corn bran (bran); or 4) corn steep liquor (steep). The study had four periods, each lasting 23 days. The first 18 days were for diet adaptation, and ruminal, duodenal, and fecal samples were collected from days 19 to 23. The Bottom Line: Corn steep liquor contributed to greater digestibility percentages, while corn germ meal and corn bran treatments were similar with respect to digestibility of most nutrients.
Keywords: digestibility; high forage diet; wet corn gluten feed